2021
DOI: 10.1177/1941738120986555
|View full text |Cite
|
Sign up to set email alerts
|

Early Sport Specialization Linked to Throwing Arm Function and Upper Extremity Injury History in College Baseball Players

Abstract: Background: Evidence suggests that shoulder and elbow injuries account for 31% to 37% of all National Collegiate Athletic Association (NCAA) baseball injuries, and up to 69% of NCAA baseball injuries are the result of noncontact and overuse mechanisms. Early sport specialization may contribute to the high rates of upper extremity injuries in college baseball players. Hypothesis: Higher specialization by age 13 years would be associated with worse subjective throwing arm function and a greater history of should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Our findings similarly affirmed a past study that reported KJOC median scores based on the age of baseball specialization, which identified no significant differences in KJOC scores based on whether the athlete was low, moderate, or highly specialized in baseball by age 13 years. 8 Our study differed from previous studies in that we assessed baseball specialization status based on different time periods rather than specific age. A significant percentage (27.6%) of participants in our study reported never specializing in baseball through high school during their youth career.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our findings similarly affirmed a past study that reported KJOC median scores based on the age of baseball specialization, which identified no significant differences in KJOC scores based on whether the athlete was low, moderate, or highly specialized in baseball by age 13 years. 8 Our study differed from previous studies in that we assessed baseball specialization status based on different time periods rather than specific age. A significant percentage (27.6%) of participants in our study reported never specializing in baseball through high school during their youth career.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies suggested that early specialization happens at high rates between the ages of 12 and 15 years, whereas medical experts encourage delaying single sport specialization as long as possible. 3,8 We found that 31.3% of athletes specialized in baseball for the first time between the middle school to early high school grade periods. A similar percentage (27.6%) reported never specializing in baseball during their youth career.…”
Section: Discussionmentioning
confidence: 83%
“…0 to 1 points, low specialization 2 points, moderate specialization 3 points, high specialization Although most parents of adolescent athletes believe early specialization will increase their child's baseball abilities "quite a bit" or "a great deal" (12), ESS has been shown to increase injury risk, increase rates of burnout, and lower rates of lifelong sports participation (13). Croci et al (14) identified those college baseball players who had highly specialized by 13 years were more likely to have a history of upper extremity injury than players who were low/moderate specialization and reported worse subjective throwing arm function. This has been observed in the Little League population and high school population, as well as with players of high sport specialization demonstrating worse throwing arm health compared with low-specialization players (15,16).…”
Section: Early Sport Specializationmentioning
confidence: 99%
“…A number of studies have looked at factors related to injury in the youth baseball population over the past year ranging in topics from; early sport specialization (ESS) (12)(13)(14)(15)(16), pitch counts (17)(18)(19)(20)(21)(22)(23), prethrowing protocols (24,25), imaging findings (26), to body region-specific inquiries (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) in search for opportunities to reduce the risk of injury in this population. We will review a wide range of articles and their relevance to injury risk in this population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shoulder health and pathology in the overhead athlete remains a particularly important topic of scholarship today. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, in this issue, we feel very fortunate to publish the very latest:…”
mentioning
confidence: 99%